Stacking Tower Game / Stapeltoren spel - Professor Puzzle (Dublin : Professor Puzzle, 2021)
Houten variant van het bekende Jenga spel. Heb jij jouw zenuwen het beste onder controle?
Wooden version of the classic game Jenga Tower. Can you stack a block without the tower falling?
Keywords: Strategie; gezelschapsspellen